Achieving and sustaining measles elimination in Hong Kong, from 1967 to 2024: lessons to be learnt - Thomas Tsang; David N Durrheim; Yu Lung Lau; Jaime S Rosa Duque; Jeffery Ching Ho Chan (BMJ Global Health, 2025)
Following the development and roll-out of the measles vaccine in 1954, measles incidence dropped to low levels in areas where measles vaccines with high coverage were introduced. The Measles and Rubella Strategic Framework 2021–2030 developed by the Measles & Rubella Initiative aims to eliminate measles globally by 2030. However, there has been a resurgence of measles cases after the COVID-19 pandemic in many countries, including some in the Western Pacific Region. This review describes the journey from 1967, when Hong Kong introduced a single-dose regimen, to 2024 when Hong Kong had been experiencing an increase in imported measles cases despite being verified to have achieved measles elimination in 2016. Hong Kong’s experience in maintaining high vaccination coverage and comprehensive surveillance may provide an exemplary framework for other countries in the Western Pacific Region.